2018
DOI: 10.2147/ijn.s151110
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of exosomes derived from <em>Toxoplasma gondii</em> and their functions in modulating immune responses

Abstract: Introduction Exosomes are nanograde membrane-bound vesicles secreted from most cell types through the fusion of multivesicular bodies with plasma membranes. Some of these exosomes are well defined, and are known to have immunomodulatory properties as well as play critical roles in intercellular communications. In this study, we characterized the exosomes derived from Toxoplasma gondii and their functions in aspect of immune responses. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 36 publications
8
78
0
1
Order By: Relevance
“…These findings are correlated with other studies that described the participation of EVs in immune response purified from other pathogens (viruses, bacteria, fungi, and parasites) in modulation of the host immune system . In these pathogens, EVs present a complex of molecules considered pathogenic for the infected host .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings are correlated with other studies that described the participation of EVs in immune response purified from other pathogens (viruses, bacteria, fungi, and parasites) in modulation of the host immune system . In these pathogens, EVs present a complex of molecules considered pathogenic for the infected host .…”
Section: Discussionsupporting
confidence: 88%
“…Toxoplasma gondii infection alters cell proliferation mechanisms of infected cells, and exosomes secreted by T. gondii ‐infected cells can mediate such changes to neighbouring cells . Recently, Li et al characterized T. gondii exosomes and showed that they can modulate the host immune response. At the same time, Wowk et al demonstrated the first proteomic profile of T. gondii exosomes, containing a wide range of proteins, including the secretory proteins used by tachyzoites for invasion and posterior replication within host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding on T. gondii, proteomic profile of exosomes containing a wide range of proteins [29]. T. gondii derived-EVs (exosomes and microvesicles) contain miRNA and they were immunologically recognized by host immune response inducing humoral and cellular responses as IL-10, TNF-α, and iNOS [30,31]. Exosomes excreted by infected host cells constituted an effective non-cellular vaccine with antigen and adjuvant properties for the immune response as well as, immunization [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes have emerged as a ubiquitous mechanism for transferring information between cells and organisms across all three kingdoms of life. 67,68 Initially described in animal cells as a general signaling pathway that allows communication between tumor and distal tissue during metastases, exosomes have also been shown to function in immune surveillance in plant cells during host-pathogen interactions, [69][70][71][72] and we propose that exosomes could also contribute to the regulation of mutualistic interactions.…”
Section: Exosomes As Signaling Shuttles From Inter-cellular Communicmentioning
confidence: 86%